Spin–Electric Coupling in a Cobalt(II)‐Based Spin Triangle Revealed by Electric‐Field‐Modulated Electron Spin Resonance Spectroscopy. Issue 16 (9th March 2021) - Kintzel, Benjamin; Fittipaldi, Maria; Böhme, Michael; Cini, Alberto; Tesi, Lorenzo; Buchholz, Axel; Sessoli, Roberta; Plass, Winfried
Abstract: A cobalt(II)‐based spin triangle shows a significant spin–electric coupling. [Co3 (pytag)(py)6 Cl3 ]ClO4 ⋅3 py crystallizes in the acentric monoclinic space group P21 . The intra‐triangle antiferromagnetic interaction, of the order of ca. −15 cm −1 (H =−JSa Sb ), leads to spin frustration. The two expected energy‐degenerate ground doublets are, however, separated by a few wavenumbers, as a consequence of magnetic anisotropy and deviations from threefold symmetry. The Co3 planes of symmetry‐related molecules are almost parallel, allowing for the determination of the spin–electric properties of single crystals by EFM‐ESR spectroscopy. The spin–electric effect detected when the electric field is applied in the Co3 plane was revealed by a shift in the resonance field. It was quantified as ΔgE /E=0.11×10 −9 m V −1, which in terms of frequency corresponds to approximately 0.3 Hz m V −1 . This value is comparable to what was determined for a Cu3 triangle despite the antiferromagnetic interaction being 20 times larger for the latter. Abstract : This contribution describes the observation of spin–electric coupling utilizing electric‐field‐modulated ESR (EFM‐ESR) spectroscopy for single‐crystals of a spin triangle which is characterized by the strong magnetic anisotropy of the individual cobalt(II) centers and a pronounced sensitivity of the molecular energy levels on the relative orientation of their magnetic axes as well as the exchange coupling between them.